Effects of subthalamic nucleus stimulation on emotional prosody comprehension in Parkinson's disease. - Carolin Brück; Dirk Wildgruber; Benjamin Kreifelts; Rejko Krüger; Tobias Wächter (PLoS ONE, 2011)
BACKGROUND: Although impaired decoding of emotional prosody has frequently been associated with Parkinson's disease (PD), to date only few reports have sought to explore the effect of Parkinson's treatment on disturbances of prosody decoding. In particular, little is known about how surgical treatment approaches such as high frequency deep brain stimulation (DBS) affect emotional speech perception in patients with PD. Accordingly, the objective of this study was to evaluate the effect of subthalamic nucleus (STN) stimulation on prosody processing. METHODOLOGY/PRINCIPAL FINDINGS: To this end the performance of 13 PD patients on three tasks requiring the decoding of emotional speech was assessed and subsequently compared to the performance of healthy control individuals. To delineate the effect of STN-DBS, all patients were tested with stimulators turned on as well as with stimulators turned off. Results revealed that irrespective of whether assessments were made "on" or "off" stimulation, patients' performance was less accurate as compared to healthy control participants on all tasks employed in this study. However, while accuracy appeared to be unaffected by stimulator status, a facilitation of reactions specific to highly conflicting emotional stimulus material (i.e. stimulus material presenting contradicting emotional messages on a verbal and non-verbal prosodic level) was observed during "on" stimulation assessments. CONCLUSION: In sum, presented results suggest that the processing of emotional speech is indeed modulated by STN-DBS. Observed alterations might, on the one hand, reflect a more efficient processing of highly conflicting stimulus material following DBS. However, on the other hand, given the lack of an improvement in accuracy, increased impulsivity associated with STN stimulation needs to be taken into consideration.